Syaria Law “Jinayah” Based on Taurat, Zabur, Injil, Al Qur’an, Hadist, Ijma, Qiyas, Statuta Roma - Widiastutik, Farah Diba Setiana (Proceeding International Conference on Religion, Science and Education, 2025)
This world begun because our Allah thet created, and this world will ended because our Allah destroy it. When Allah created human Prophet Adam A.S and Eve until Allah created Prophet Muhammad SAW, all of human just used KitabAllah or Syaria law being foundation of human life. First Prophet that being Rasul is Prophet Musa A.S and Allah give him Taurat or Torah at Ibrani language. Second Rasul is Prophet Daud A.S and Allah give him Zabur or Zohar. Third Rasul is Prophet Isa A.S or Yesus at Ibrani language and Allah give him an Injil. Last Rasul is Prophet Muhammad SAW and Allah give him Al Qur’an. Since Prophet Musa A.S until Prophet Muhammad SAW and Kulafaur Rasyidin all of human just used Syaria law for being foundation of their life. Now we had degradaded Iman and Islam we can saw if many kingdom that change their government system being republic and change their law from syarial law being human law. Country that still used Syaria law based on Allah Kitab just Saudi Arabia, Qatar, Iran, Malaysia, Brunai Darrusalam, Afganistan, Sudan, Nigeria although their Syaria law just based on Al Qur’an, Hadist, Ijma, Qiyas and no one from Isaiah zona that used Syaria law for being foundation of human life. This fact maked me want to maked this research Syaria law based on Taurat, Zabur, Injil, Al Qur’an, hadist, Ijma, Qiyas. The aim from my research is complete law book and SOP law and firm based on Complete KitabAllah to handle contract and problems between Isaiah and Mouslem. This research I maked since April 2019 untill Oktober 2024 at Semarang Central Java Indonesia. Data from this research consist of Primary data from Imam Rabi, Paus, and Makkah. Secondary data from this research come from Taurat, Zabur, Injil, Al Qur’an, Hadist, Ijma, Qiyas, Statuta Roma. Analize data for this research I used Descriptive Kualitatif. Benefit from this research are forever royalty from SOP Law ad Firm, SOP Law school and university, Law book. Result from this research are law book based on Taurat, Zabur, Injil, Al Qur’an, Hadist, Ijma, Qiyas, Statuta Roma.